BPJS Patient Experiences Regarding Administrative Services at Jakarta Islamic Hospital Sukapura, Kelapa Gading - Ellynia; Ramba, Hardin La; Khofipah (JURNAL KESEHATAN, SAINS, DAN TEKNOLOGI (JAKASAKTI), 2025)
Administrative services are a crucial component of the healthcare system, especially for patients using Indonesia’s National Health Insurance (BPJS). Despite the implementation of digital tools such as the Mobile JKN application, many patients still report complaints related to long waiting times, unclear procedures, and a lack of empathy and responsiveness from administrative staff. This study aims to explore the experiences of BPJS patients regarding administrative services at Jakarta Islamic Hospital Sukapura, Kelapa Gading. The research employed a qualitative approach with a descriptive phenomenological method. Participants were selected using purposive sampling based on inclusion criteria such as age (20–60 years), being a current inpatient or outpatient, and being able to communicate effectively. Data were collected through in-depth interviews and analyzed using thematic analysis. The study identified two main themes: responsiveness of administrative staff and empathy during service delivery. Most participants perceived administrative services as inefficient, citing long waiting times, insufficient information, and unresponsive staff when addressing patient concerns. Additionally, the level of empathy demonstrated by staff was considered inadequate, as some patients felt misunderstood or unheard. The study recommends enhancing staff training, improving the hospital’s information systems, and conducting regular evaluations of service quality. Increasing responsiveness and empathy is expected to foster a more positive experience for BPJS patients and contribute to greater patient satisfaction